Produksi, Hara N dan P Terangkut akibat Aplikasi Berbagai Jenis Biochar dan Pupuk P pada Pertanaman Jagung Manis (Zea Mays Saccharata Sturt.) di Lahan Tanah Ultisol Natar Lampung Selatan - Septi Nurul Aini; Ridho Setiawan; Jamalam Lumbaraja; Sarno Sarno; Liska Mutiara Septiana (Journal of Tropical Upland Resources (J. Trop. Upland Res.), 2022)
Field and laboratory research was conducted to determine the effect of the application of various types of biochar and P fertilizer on the nutrients N and P transported, and sweet corn  (Zea mays Saccharata Sturt.) production in Ultisol Natar soil, South Lampung. This experiment was arranged using a factorial Randomized Block Design (RBD) with 2 factors. The first factor was the provision of various kinds of biochar (B), viz:  1. without biochar (B0); 2. rice husk biochar 10 Mg ha-1 (B1); 3. corncob biochar 10 Mg ha-1 (B2); 4. cassava stem biochar 10 Mg ha-1 (B3). The second factor was phosphorus fertilizer treatment, viz: 1. no P fertilizer (P0); 2. TSP fertilizer application of 335 kg ha-1 (P1). Each treatment was repeated three times. The field research was conducted at the Integrated Field Laboratory of the Faculty of Agriculture of the University of Lampung and the chemical analysis of soil and plants was carried out at the Laboratory of Soil Science, Faculty of Agriculture, University of Lampung. The results showed that the application of various types of biochar and fertilization was able to increase the availability of nutrients and uptake of N, P and C-Organic in the soil, but could not increase CEC and soil pH in sweet corn cultivation in Ultisol soil. There is a correlation or relationship between N-total and P-available soil with N, P absorbed in sweet corn cultivation in Ultisol soil.